IMPLEMENTASI MODEL PEMBELAJARAN TALKING CHIPS TERHADAP HASIL BELAJAR SISWA - Abdul Manaf (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to describe the implementation of the Talking Chips learning model in improving student learning outcomes. The study used a qualitative approach with a descriptive research type. The research subjects consisted of teachers and students who participated in the learning process using the Talking Chips model. Data were collected through observation, interviews, documentation, and analysis of student learning outcomes. Data validity was carried out using source and technique triangulation techniques, while data analysis used an interactive model that included data reduction, data presentation, and drawing conclusions. The results showed that the application of the Talking Chips learning model was able to create a more active, collaborative, and communicative learning atmosphere. Students had equal opportunities to express opinions, discuss, and participate in learning so that learning engagement increased. Increased activeness and interaction during learning had a positive impact on material understanding and student learning outcomes. In addition, teachers assessed that the Talking Chips model could improve student cooperation, self-confidence, and responsibility in group activities. Thus, the Talking Chips learning model was effectively implemented as an alternative student-centered learning to support improved learning outcomes.